2017
DOI: 10.1002/chem.201704102
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Stable Ruthenium(IV) Ketimido Complexes by Oxidative Addition of Oxime Esters to Ruthenium(II): Reactivity Studies Based on Electronic Properties of the Ru−N Bond

Abstract: The reaction of an oxime ester with [Ru(PPh ) X ] proceeded smoothly at room temperature to afford a stable Ru ketimido complex as oxidative adduct. The structure of the complex was unambiguously determined by X-ray crystallographic analysis, which showed an almost linear Ru-N-C array. The electronic properties of the nitrogen atom were estimated by DFT calculations, and the results suggested double-bond character of the Ru-N bond. Kinetic studies and consideration of the substituent effect on the oxime ester … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…14 In fact, Okamoto and Ohe reported that the r value for the oxidative addition of the oxime ester N-O bond to ruthenium is +0.19 at the oxime carbon. 15 Thus, the N-O bond cleavage process in the present rearrangement reaction can be regarded as an oxidative addition with inverse electron ow. On the other hand, the inverse electron ow in oxidative addition observed in the present reaction is in good agreement with the report by Amgoune and Bourissou; the r value for the oxidative addition of para-substituted iodoarenes to cationic Au(I) complex is −1.09.…”
Section: Resultsmentioning
confidence: 95%
“…14 In fact, Okamoto and Ohe reported that the r value for the oxidative addition of the oxime ester N-O bond to ruthenium is +0.19 at the oxime carbon. 15 Thus, the N-O bond cleavage process in the present rearrangement reaction can be regarded as an oxidative addition with inverse electron ow. On the other hand, the inverse electron ow in oxidative addition observed in the present reaction is in good agreement with the report by Amgoune and Bourissou; the r value for the oxidative addition of para-substituted iodoarenes to cationic Au(I) complex is −1.09.…”
Section: Resultsmentioning
confidence: 95%
“…The same research group was indeed able to further streamline this idea and use the same class of substrates to access highly subsituted pyridines 49, [50] and the authors also suggested that a Ru-ketimido complex was a possible intermediate species (Scheme 12a), as in the case of oxime esters (Scheme 3e). [13] Further confirming the exploitability of this fact, Ohe and coworkers were able to utilize Rh and Co catalysts to access 2H-pyrroles 50 and azabicyclic cyclopropanes 51, respectively (Scheme 12a). [51] It is very intriguing how these different catalytic conditions can greatly influence the reaction outcome.…”
Section: Decarboxylative Transformationsmentioning
confidence: 81%
“…As in the case of Pombeiro's rhenium complex 8, [10] the short bond distance (1.790 Å) claimed for a significant double bond character, which was supported by natural bond orbital (NBO) analysis (Scheme 3e). [13] The group of Love isolated the Ni(II) complex 16 resulting from the oxidative addition of [(dtbpe)Ni(0)] complex (dtbpe = 1,2bis(di-tert-butylphosphino)ethane) into the N-O bond of Nadamantyl oxaziridine. This complex proved to be stable enough at -30 °C to grow crystals (Scheme 3f), but decomposed at higher temperatures.…”
Section: Transition Metals Oxidative Addition In the N-o σ Bondmentioning
confidence: 99%
“…In this context, we envisioned that alkene-tethered oxime ethers would be converted into nitriles in the presence of a transition metal catalyst, proving a novel method for the catalytic synthesis of nitriles from oxime derivatives as shown in Scheme . Initially, the oxidative addition of a N–O bond or an oxime C–H bond of the alkene-tethered oxime ethers to a low valent metal center would occur via intermediate I to generate intermediate II or III . As shown in intermediate I , we speculate that the oxidative addition step might be accelerated by the directing effect of the alkene group to the metal center .…”
mentioning
confidence: 88%